Evaluation of Quality of Life in Breast Cancer Patients: A Cross-Sectional Comparative Study between Targeted Therapy and Conventional Chemotherapy - Pratama, Kharisma Jayak; Luthfiyanti, Niken (Sciences of Pharmacy, 2025)
Breast cancer is one of the most common cancers worldwide, with treatment often involving conventional therapies such as chemotherapy. Although effective, chemotherapy is often accompanied by significant side effects and reduces patients' quality of life. Targeted therapy, which targets specific molecular mechanisms in cancer cells, offers the potential to address these issues with higher efficacy and fewer side effects. This study aims to compare the quality of life of breast cancer patients receiving targeted therapy with chemotherapy. The study design used a comparative cross-sectional design involving 60 patients (30 receiving targeted therapy, 30 receiving chemotherapy) selected via consecutive sampling at RSUD Moewardi in Surakarta (January–June 2025). Data were collected using the validated Indonesian version of the EORTC QLQ-C30 questionnaire. Statistical analysis included parametric t-tests and non-parametric Mann-Whitney U tests. The study results showed that the targeted therapy group had better role functioning (p = 0.047.95% CI=0.044-0.053) and significantly lower pain (p= 0.001.95% CI=0.000-0.002) and nausea (p = 0.019.95% CI=0.016-0.021) symptoms compared to chemotherapy. Global health status did not differ significantly (p= 0.545.95% CI=0.536-0.556). Age (p = 0.012.95% CI=0.08-0.012) and stadium (p = 0.001.95% CI=0.001-0.003) significantly influenced global QoL. Targeted therapy provided advantages in functional aspects and specific symptoms, although not in global QoL. A key study limitation is its cross-sectional design, which prevents the establishment of causal relationships between the type of therapy and quality of life outcomes.